Post-Traumatic Growth After the Drug-Related Death of a Loved One: Understanding the Influence of Self-Compassion and Hope. (July 2022) - Sperandio, Katharine R.; Gutierrez, Daniel; Kirk, Meghan; Lopez, Jessica; Nathaniel Mason, W.
The interaction between self-compassion, hope, and posttraumatic growth (PTG) following the loss of a loved one to a drug related death (DRD) has been largely unexplored in the current literature. This study examines the interaction between the constructs of hope and self-compassion as they impact PTG among those who are in bereavement from a DRD. For the purposes of this study a "loved one" is defined as anyone who had a meaningful relationship with the person who is now deceased. We examined the associations between self-compassion, PTG and hope using structural equation modeling with a sample of 292 individuals who experienced the DRD of a loved one. Our analysis shows that self-compassion serves as a predictor for PTG when operating independently from hope. When the construct of hope is introduced, it serves as a powerful mediator on the relationship between self-compassion and PTG following bereavement by a DRD. These results suggest that the facilitation of the psychospiritual constructs of hope and self-compassion during the counseling process following the loss of a loved one to a DRD can serve to support PTG.